2010
DOI: 10.1590/s0037-86822010000600002
|View full text |Cite
|
Sign up to set email alerts
|

Decline in prevalence and asymmetric distribution of human T cell lymphotropic virus 1 and 2 in blood donors, State of Minas Gerais, Brazil, 1993 to 2007

Abstract: Introduction: Human T cell lymphotropic virus types 1 and 2 (HTLV-1/2) are endemic in Brazil and are screened for in transfusion services since 1993. This study evaluated the evolution of the prevalence of HTLV-1 and 2 in blood donors of the Hemominas Foundation from 1993 to 2007, and its geographical distribution in State of Minas Gerais, Brazil. Methods: The Hemominas Foundation is a centralized blood center in Minas Gerais, Brazil. The sources of data were the Hemominas Foundation Technical Bulletin and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…This was also observed in other studies,6., 13., 15. with prevalences among males of 54.95%, 59.4%, and 57.8%. However, this is usually explained by the higher numbers of male donors than female donors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was also observed in other studies,6., 13., 15. with prevalences among males of 54.95%, 59.4%, and 57.8%. However, this is usually explained by the higher numbers of male donors than female donors.…”
Section: Discussionsupporting
confidence: 89%
“…At HEMOACRE, a value of 0.11% was observed using the same kit (Elisa Murex®), and values ranging from 0.08% to 1.80% were found between 1989 and 1996, which were also within the national average 7 . At HEMOMINAS, a value of 0.1% was observed between 1993 and 2007 using ELISA 13 . At Hemonúcleo de Patos, in the state of Paraíba, Braga et al 14 found a prevalence of 0.025% of HTLV-1 between 2002 and 2011.…”
Section: Discussionmentioning
confidence: 88%
“…Seroprevalence rates were in the order of 1 to 2 per thousand first time donors which is higher than in the United States and Europe but lower than in the Brazilian general population (24) .…”
mentioning
confidence: 74%
“…The huge number of HTLV-1-infected men among blood donors could be a consequence of the high number of donors of this gender. An age-and-gender-cohort effect due to the characteristics of blood donors worldwide could not be excluded [12].…”
Section: Discussionmentioning
confidence: 99%